Biological assessment of uncoated and hydroxyapatite-coated ferum as biodegradable scaffold for hard tissue regeneration - Nurizzati Mohd. Daud, 1988- author; Hendra Hermawan, supervisor; Mohammed Rafiq Abdul Kadir, supervisor; Fakulti Biosains dan Kejuruteraan Perubatan (2014)
Thesis (Sarjana Kejuruteraan (Bioperubatan)) - Universiti Teknologi Malaysia, 2014